The Nonmonotonic Investment–Cash Flow Sensitivity and Business Life Cycle: Evidence from An Emerging Market - Thai Thi Hong An,; Ha Le Hong Ngoc, (Asian Academy of Management Journal of Accounting and Finance, 2025)
This article aims to investigate the non-linear correlation between investment and cash flow. Drawing on a sample of 669 Vietnamese publicly listed firms from 2010 to 2021, the study tests two hypotheses concerning the investment–cash flow relationship, employing a two-step system-GMM approach. The sensitivity of investment to cash flow is examined across different financial scenarios and business stages. The results demonstrate a U-shaped investment-cash flow relationship, which consistently holds across various firms’ financial positions and ownership structures. Interestingly, this pattern is absent under the influence of the COVID-19 pandemic. When considering the business life cycle, the results indicate that while companies in the introduction and expansion phases exhibit the inverted U-shaped sensitivity, those in the maturity and decline stages display a U-pattern. These outcomes enrich the existing corporate literature and offer significant practical insights for investors, firm managers, and policy-setting parties, particularly within the emerging market context.